Misdiagnosis of gestational trophoblastic neoplasia as ectopic pregnancy: A 15-year retrospective study - Xiao, Ping; Guo, Tao; Yin, Rutie (Frontiers in Medicine, 2022)
Bankground: Gestational trophoblastic neoplasia is an uncommon disease, whose clinical manifestations are similar to ectopic pregnancy, thus some rare pelvic lesion can be misdiagnosed as ectopic pregnancy. Aims: This study was presented to investigate the characteristics of gestational trophoblastic neoplasia misdiagnosed as ectopic pregnancy and reduce the misdiagnosis. Methods: The clinicopathological data for 14 cases of gestational trophoblastic neoplasia misdiagnosed as ectopic pregnancy at West China Second Hospital Sichuan University from January 2006 to December 2020 were retrospectively analyzed. Results: The main clinical manifestations were menopause, abnormal vaginal bleeding, and abdominal pain. At initial diagnosis, the serum hCG level was greater than 10,000 mIU/mL in 5 patients and less than 10,000 mIU/mL in 7 patients, and a positive urine pregnancy test alone was found in 2 patients. Vaginal ultrasonography showed no abnormalities in 7 cases, adjuncts occupying space in 5 cases, and tubal thickening in 2 cases. Clinical stage: 3 cases were stage I, 3 were stage II, 7 were stage III, and 1 case was stage IV (liver and spleen metastases). The median FIGO prognostic score was 13.5 points (12–21 points), with 9 cases having a score greater than 13 points (very high risk). After chemotherapy alone or in combination with surgery, all patients survived, with a median follow-up of 84 months (23–102 months). Conclusion: In patients with an abnormally elevated serum hCG level but no signs of pregnancy either intrauterine or extrauterine, vigilance should be exercised to avoid misdiagnosis and expedite treatment.